Assessment of Intraoperative Blood Loss at Different Surgical Stages During Posterior Spinal Fusion Surgery in the Treatment of Adolescent Idiopathic Scoliosis. Issue 9 (May 2016) - Chiu, Chee Kidd; Chan, Chris Yin Wei; Aziz, Izzuddin; Hasan, M. Shahnaz; Kwan, Mun Keong
Abstract : Study Design: Prospective clinical study. Objective: To analyze the amount of blood loss at different stages of Posterior Instrumented Spinal Fusion (PSF) surgery in adolescent idiopathic scoliosis (AIS) patients. Summary of Background Data: Knowing the pattern of blood loss at different surgical stages may enable the surgical team to formulate a management strategy to reduce intraoperative blood loss. Methods: One hundred AIS patients who underwent PSF from January 2013 to December 2014 were recruited. The operation was divided into six stages; stage 1—exposure, stage 2—screw insertion, stage 3—release, stage 4—correction, stage 5—corticotomies and bone grafting, and stage 6—closure. The duration and blood loss at each stage was documented. The following values were calculated: total blood loss, blood loss per estimated blood volume, blood loss per minute, blood loss per vertebral level fused, and blood loss per minute per vertebral level fused. Results: There were 89 females and 11 males. The mean age was 17.0 ± 5.8 years old. Majority (50.0%) were Lenke 1 curve type. The mean preoperative major Cobb angle was 64.9 ± 15.0°. The mean number of levels fused was 9.5 ± 2.3 levels. The mean operating time was 188.5 ± 53.4 minutes with a mean total blood loss 951.0 ± 454.0 mLs. The highest mean blood loss occurred at stage 2 (301.0 ± 196.7 mL), followed by stage 4 (226.8 ± 171.2 mL) and stage 5 (161.5 ± 146.6 mL). The highest mean blood loss per minute was at stage 5 (17.1 ± 18.3 mL/min), followed by stage 3 (12.0 ± 10.8 mL/min). The highest mean blood loss per vertebral levels fused was at stage 2 (31.0 ± 17.7 mL/level), followed by stage 4 (23.9 ± 18.1 mL/level) and stage 5 (16.6 ± 13.3 mL/level). Conclusion: All stages were significant contributors to the total blood loss except exposure (stage 1) and closure (stage 6). Blood loss per minute and blood loss per minute per level was highest during corticotomies (stage 5), followed by release (stage 3). However, the largest amount of total blood loss occurred during screw insertion (stage 2). Level of Evidence: 2